2018
DOI: 10.3389/fchem.2018.00345
|View full text |Cite
|
Sign up to set email alerts
|

New Properties of a Bioinspired Pyridine Benzimidazole Compound as a Novel Differential Staining Agent for Endoplasmic Reticulum and Golgi Apparatus in Fluorescence Live Cell Imaging

Abstract: In this study, we explored new properties of the bioinspired pyridine benzimidazole compound B2 (2,4-di-tert-butyl-6-(3H-imidazo[4,5-c]pyridine-2-yl)phenol) regarding its potential use as a differential biomarker. For that, we performed 1D 1HNMR (TOCSY), UV-Vis absorption spectra in different organic solvents, voltammetry profile (including a scan-rate study), and TD-DFT calculations that including NBO analyses, to provide valuable information about B2 structure and luminescence. In our study, we found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The SDS, present in the gel, could interfere with a cationic dye due to its anionic nature, as previously reported ( Sundaram et al, 2012 ). Concerning the free ligand B2 , which is also luminescent by itself ( Carreno et al, 2016a ; Berrios et al, 2018 ; Llancalahuen et al, 2018 ), we observed an apparent interaction with the gel’s whole matrix, showing intense luminescence even after the wash with water. When DMSO, instead of water, was used to remove unbound B2 , we could observe some bands of high molecular weight (top of the lane), which generally retain a high amount of dye, in comparison with bands found at the bottom of the lane (low molecular weight).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The SDS, present in the gel, could interfere with a cationic dye due to its anionic nature, as previously reported ( Sundaram et al, 2012 ). Concerning the free ligand B2 , which is also luminescent by itself ( Carreno et al, 2016a ; Berrios et al, 2018 ; Llancalahuen et al, 2018 ), we observed an apparent interaction with the gel’s whole matrix, showing intense luminescence even after the wash with water. When DMSO, instead of water, was used to remove unbound B2 , we could observe some bands of high molecular weight (top of the lane), which generally retain a high amount of dye, in comparison with bands found at the bottom of the lane (low molecular weight).…”
Section: Resultsmentioning
confidence: 83%
“…B2 [2,4-di- tert -butyl-6-(3H-imidazo[4,5-c]pyridine-2-yl)phenol] presents promising features regarding its use as a fluorophore for diverse biological applications. B2 is an excellent luminescent cell dye for confocal microscopy, showing differential staining for the endoplasmic reticulum and the Golgi apparatus in epithelial cell lines ( Carreno et al, 2016a ; Llancalahuen et al, 2018 ) and staining walled cells, such as yeasts ( Candida albicans ), Gram-negative bacteria ( Salmonella enterica and Escherichia coli ), and Gram-positive bacteria ( Lactobacillus kunkeei ) for confocal microscopy ( Carreno et al, 2016a ; Berrios et al, 2018 ). Nevertheless, despite these remarkable properties, B2 lacks sulfonate groups (–SO 3 − ) and positively charged groups, suggesting that this compound cannot interact with proteins to permit an efficient protein staining.…”
Section: Introductionmentioning
confidence: 99%
“…The PBI and its derivative molecules, mainly the metal clusters of PBI, have shown bioactivity that is widely used in various fields of chemistry. [33][34][35][36][37][38][39][40][41][42][43][44][45] The structural tuning of dispersion interactions using PBI-Ar 1-3 complexes will serve as a model system to understand biological processes such as analgesia, anesthesia, tissue protection and a varied range of other clinical effects. [42][43][44][45] Recently, the shift in origin-band and the change in intermolecular vibrational modes were used to identify the docking positions of Ar atoms on the PBI molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, surgical specialists urgent need an effective tool to easily distinguish between tumor and normal tissue during surgery. Fluorescence technology has been paid unprecedented attention (Blum et al, 2007 ; Paulick and Bogyo, 2008 ; Asanuma et al, 2015 ; Ofori et al, 2015 ; Cheng et al, 2016 ; Gu et al, 2016a , b ; Hu et al, 2016 ; Chen et al, 2017 ; He et al, 2017 ; Liu et al, 2017a , b , c ; Wang et al, 2017a , 2018 ; Yin et al, 2017 ; Kuriki et al, 2018 ; Li et al, 2018b ; Llancalahuen et al, 2018 ; Miao et al, 2018 ; Sedgwick et al, 2018 ; Shang et al, 2018 ; Verwilst et al, 2018 ), especially for medical diagnosis and treatment system (Kim et al, 2017 ; Li et al, 2017b ; Verwilst et al, 2017 ), owing to efficient identification without destructive in vivo . Thus, it is of great medical significance to develop fluorescent probe that can assist clinician for imaging and resection of tumor.…”
Section: Introductionmentioning
confidence: 99%